Biomineralization in metakaolin modified cement mortar to improve its strength with lowered cement content - Li, M.; Zhu, X.; Mukherjee, Abhijit; Huang, M.; Achal, V. (Elsevier BV, 2017)
© 2017 Elsevier B.V.The role of industrial byproduct as supplementary cementitious material to partially replace cement has greatly contributed to sustainable environment. Metakaolin (MK), one of such byproduct, is widely used to partial replacement of cement; however, during cement replacement at high percentage, it may not be a good choice to improve the strength of concrete. Thus, in the present study, biocement, a product of microbially induced carbonate precipitation is utilized in MK-modified cement mortars to improve its compressive strength. Despite of cement replacement with MK as high as 50%, the presented technology improved compressive strength of mortars by 27%, which was still comparable to those mortars with 100% cement. The results proved that biomineralization could be effectively used in reducing cement content without compromising compressive strength of mortars. Biocementation also reduced the porosity of mortars at all ages. The process was characterized by SEM-EDS to observe bacterially-induced carbonate crystals and FTIR spectroscopy to predict responsible bonding in the formation of calcium carbonate. Further, XRD analysis identified bio/minerals formed in the MK-modified mortars. The study also encourages combining biological role in construction engineering to solve hazardous nature of cement and at same time solve the disposal problem of industrial waste for sustainable environment.